The Prevalence of Vitamin D Deficiency and Its Related Factors Among Female Staff of Gonabad University of Medical Sciences, Gonabad City, Iran, in 2019 - Sedigheh Niazi; Abdulghader Taene; Mojtaba Kianmehr; Abbasali Abbasnezhad; Mohammad Matlabi (Gonabad University of Medical Sciences, 2020)
Background: Vitamin D (VitD) plays a significant role in human health, survival, and fertility. It is necessary for calcium absorption and bone growth and the regulation of the immune system. This study aims to determine the prevalence of VitD deficiency and the factors affecting it in women working in the campus of Gonabad University of Medical Sciences, Gonabad City, Iran. Methods: In this cross-sectional analytical study, 70 women working on the campus of Gonabad University of Medical Sciences in 2019 were selected by the census method. After obtaining their consent forms, the researcher-made checklist was completed by the participants. The serum levels of 25-hydroxycholecalciferol (25-OH D3) were the index for measuring VitD. The significance level is set below 0.05. Results: The Mean±SD level of VitD in the research units was 13.67±22.5 ng/mL. About 12.85% of the samples had severe deficiency (less than 10 ng/mL), 32.85% had moderate deficiency (10-20 ng/mL) and 31.42% had mild deficiency (20-30 ng/mL). The prevalence of VitD deficiency was lower in people with a history of physical activity, and those with a history of taking supplements. Also, the highest VitD deficiency was observed in the age group of older than 40 years. Conclusion: According to the results, the prevalence of VitD deficiency in the study population was high because 45.7% of the subjects had severe and moderate VitD deficiency.